Pelaksanaan Pendidikan Kesehatan Bagi Tunagrahita Ringan di SLB Al-Azhar Bukittinggi - Eldawita Eldawita; Kasiyati Kasiyati (Universitas Negeri Padang, 2021)
This study discusses the implementation of health education at SLB Al-Azhar Bukittinggi for mild mentally retarded students. This study uses a descriptive method with a qualitative approach. Data collection techniques with observation, interviews and documentation studies. In this study, the subjects were UKS guidance teachers, PJOK teachers, school principals and students. The results showed that the implementation of health education activities at SLB Al-Azhar Bukittinggi was programmed well and went well. However, during the pandemic corona virus disease (covid-19) the implementation did not work because at that time students were learning from home. In carrying out the school health education program, it collaborates with the puskesmas. The puskesmas provides health education education for schools through teachers and students. With the existence of school health education becomes cleaner and students through teachers know about health and can apply it. Although there are obstacles experienced in its implementation, schools can overcome them.